Scientific Paradigms in Maritime Technological Innovation: Leadership and Epistemological Decision-Making - Binsar Halomoan. T; Dimas Pradipta; Elza Ratna Perbata; Herna Y. Manik; Jarry Rinaldy; Kerin Rakatejamukti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The maritime industry is undergoing rapid technological transformation, yet the role of scientific paradigms in shaping technological decision-making remains underexplored. This study examines how epistemological reasoning influences leadership approaches to technological innovation in maritime business management. The research is motivated by the need to bridge the gap between theory and practice, ensuring that technological advancements are implemented with structured decision-making rather than reactive adaptation. This study provides an original contribution by evaluating the intersection of leadership, epistemology, and technological adoption—a perspective largely overlooked in previous maritime innovation research. While digital transformation is widely discussed, few studies address how structured epistemological reasoning affects decision-making in technology adoption. The research seeks to answer: To what extent do scientific paradigms influence technological decision-making in maritime leadership, and what challenges hinder epistemological integration? Using a qualitative methodology, the study engages industry experts, lecturers, and postgraduate students, applying thematic and comparative analysis to explore epistemological competency development and sustainable innovation. Results indicate that leadership adaptability and epistemological literacy significantly enhance digital transformation efforts, yet barriers such as regulatory constraints and resistance to structured reasoning persist. The study concludes that embedding epistemology into maritime education and leadership training is essential for ensuring sustainable, data-driven technological decision-making in the industry.